(untitled) (Research, Society and Development, 2025)
Objective: To promote the health of indigenous children in the Kainã Village, municipality of Manaquiri (AM), contributing to health equity and the appreciation of cultural diversity in the Amazonian context, through the “Cuidar Amazônico” program. Method: Extension project developed with the Kainã indigenous population, involving nursing activities, data collection, application of questionnaires, and educational workshops. The activities included care at the health post and recreational actions in celebration of Children’s Day, focusing on health promotion and cultural integration. Results: It was observed that childhood vaccination is an essential tool for health protection, healthy development, and the reduction of health inequalities among indigenous children in Amazonas. The project fostered dialogue between scientific and traditional knowledge, strengthening active listening, respect for local culture, and the bond between the health team and the community. Conclusion: The experience demonstrated that educational and participatory actions are fundamental to strengthening indigenous child health and building care practices based on interculturality and the appreciation of traditional knowledge.